2013
DOI: 10.1007/s00431-013-2142-0
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of transcutaneous bilirubin measurement in preterm low-birth-weight neonates

Abstract: TcB has good correlation and agreement with STB in preterm low-birth-weight neonates born at ≥28 weeks of gestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…The AJO-Neo device is based on such a spectroscopy-based approach where the majority of the information is collected from the vascular bed underneath the nail plate 18 . Thus, we predicted that AJO-Neo will be able to overcome the limitations of the conventional TcB meters i.e., their limited accuracy in preterm infants 34,[36][37][38] , dark skin babies 14,[39][40][41] , neonates having phototherapy 39,[42][43][44][45][46][47] , newborns with low birth weight 48,49 , exclusively breastfed infants 34,[50][51][52] , neonates with higher postnatal age 34 and high TSB value 34,[53][54][55] , etc.…”
Section: Discussionmentioning
confidence: 99%
“…The AJO-Neo device is based on such a spectroscopy-based approach where the majority of the information is collected from the vascular bed underneath the nail plate 18 . Thus, we predicted that AJO-Neo will be able to overcome the limitations of the conventional TcB meters i.e., their limited accuracy in preterm infants 34,[36][37][38] , dark skin babies 14,[39][40][41] , neonates having phototherapy 39,[42][43][44][45][46][47] , newborns with low birth weight 48,49 , exclusively breastfed infants 34,[50][51][52] , neonates with higher postnatal age 34 and high TSB value 34,[53][54][55] , etc.…”
Section: Discussionmentioning
confidence: 99%
“…Forehead and sternum are the most commonly reported measurement sites, [11][12][13][14] performance of the bilirubinometer in other body sites after phototherapy has not been evaluated. The aim of this prospective study was to provide the missing data on the accuracy of the device in term Caucasian newborn infants who underwent phototherapy, considering four different measurement sites (exposed and unexposed) and two different modalities of phototherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Study by Chawla et al in 256 preterm neonates of <35 weeks GA for all 3 sites showed good correlation on forehead followed by abdomen and then sternum (r = 0.84, 0.72 and 0.83) 4 . Similar observations have been made by Kurokawa et al in VLBW neonates 5 .…”
Section: Discussionmentioning
confidence: 85%